An Analysis of Assertive Illocutionary Acts Used by Local Guides in Tirta Empul Temple - Sri Indrawati Ni Luh (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Language is an important factor in communication tools. By communication, people can build a good relationship. In order to make good communication, they have to understand well what the speaker says. In this case, learning speech act theory is important to cover this problem. This stud focused on classifying the types of assertive illocutionary acts used by local guides in Tirta Empul Temple and the meaning of assertive illocutionary acts conveyed by local guides in Tirta Empul Temple. The writer applied the theory proposed by Searle and Vanderveken (1985) to classify the types of assertive illocutionary acts used by local guides in Tirta Empul Temple. This research used a qualitative method to analyze the data descriptively using sentences that are already organized into paragraphs and also this research used a quantitative method to find out the frequency of types of assertive illocutionary acts used by local guides in Tirta Empul Temple. The research finding showed that there are four types of assertive used by local guides in Tirta Empul Temple: informing, stating, expressing an opinion, and reminding. Based on the data, there are 31 utterances includes types of assertive illocutionary acts found in local guide utterances in Tirta Empul Temple. Types of assertive illocutionary acts for informing become the dominant type used by local guides’ utterances. It holds (48,38%) for 15 utterances, stating (6,45%) for 2 utterances, expressing opinion (29,03%) for 9 utterances, and reminding (16,12%) for 5 utterances.